Learning Programming with Robotics Using Arduino: Practice and Interdisciplinarity - Victal, Enza; Candido, Alex (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
For various reasons, mainly social, Brazilian schools have difficulties inserting technological resources as allies for learning. Many classrooms still follow the old standard of teacher-centered classes. However, this scenario has been changing, even if slowly, and it is already seen some education institutions using mobile devices, augmented reality, digital games and robotics. Educational robotics has been gaining ground, bringing many positive arguments that justify its use, consolidating itself as a fundamental technological practice, as a tool to support learning. This article presents an experience report about robotics used as a teaching strategy for beginners of the Computer Science course. In that experiment, students used Arduino 1 to create real and accessible projects, putting the theoretical content in a playful, dynamic, attractive and immersive way.